2013
DOI: 10.1111/jvh.12210
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe, nonfulminant acute hepatitis B with lamivudine vs placebo: a prospective randomized double‐blinded multicentre trial

Abstract: Acute hepatitis B virus (aHBV) infection can lead to fulminant liver failure, which likely is prevented by early lamivudine therapy. Even nonfulminant but severe acute hepatitis B can lead to significant morbidity and impaired quality of life. Therefore, lamivudine was evaluated in patients with severe aHBV in a placebo-controlled trial. Patients with severe aHBV infection (ALT >10× ULN, bilirubin >85 μm, prothrombin time >50%) were prospectively treated with lamivudine 100 mg/day or with placebo within 8 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
(36 reference statements)
0
25
0
1
Order By: Relevance
“…Accordingly, we were able to show in case series of 6 consecutive patients with ALF due to HBV that the treatment with entecavir remarkably reduced the cell death marker within a few days, leading to a complete recovery in all treated patients [15]. However, in a prospective placebo controlled trial with patients with acute non-fulminant hepatitis B lamivudine treatment did not show a significant advantage towards survival [11]. Another study from China showed an advantage of lamivudine treatment in patients with acute to fulminant hepatitis B only in patients without systemic inflamatoric response syndrome, suggesting the therapy should be started early [16].…”
Section: Zusammenfassungmentioning
confidence: 84%
See 1 more Smart Citation
“…Accordingly, we were able to show in case series of 6 consecutive patients with ALF due to HBV that the treatment with entecavir remarkably reduced the cell death marker within a few days, leading to a complete recovery in all treated patients [15]. However, in a prospective placebo controlled trial with patients with acute non-fulminant hepatitis B lamivudine treatment did not show a significant advantage towards survival [11]. Another study from China showed an advantage of lamivudine treatment in patients with acute to fulminant hepatitis B only in patients without systemic inflamatoric response syndrome, suggesting the therapy should be started early [16].…”
Section: Zusammenfassungmentioning
confidence: 84%
“…So far, prognostic markers are not established, which may predict who will recover spontaneously and who will control the HBV virus eventually [10]. A randomized trial in severe non-fulminant acute hepatitis B, which tested lamivudine versus placebo, did not show a significant advantage for treatment; however, the numbers were small [11]. Nevertheless, no patient developed liver failure.…”
Section: Zusammenfassungmentioning
confidence: 99%
“…185 The management of acute liver failure and the indication for liver transplantation are discussed in detail in separate EASL CPGs. 151,180 Early NA treatment does not increase the risk of chronicity 181,186 ; in fact, observational data from a multicentre cohort even indicated reduced rates of chronicity, if NA treatment was initiated within 8 weeks of acute hepatitis B presentation in genotype A infected individuals.…”
Section: Acute Hepatitis B Recommendationsmentioning
confidence: 99%
“…Although lamivudine has been used to treat fulminant hepatitis in infancy and severe acute hepatitis B in adults, the efficacy in infants is still controversial due to limited case numbers. 5,6 Well-controlled clinical trials are warranted to explore the efficacy and safety of treatment in those who may benefit from early antiviral treatment. Before such evidence is available, it is still too early to apply antiviral treatment to infants with HBV infection.…”
Section: Antiviral Treatment For Hepatitis B In Infancy: Still An Issmentioning
confidence: 99%